Design and development of a multi-gripper for use in an automated robotic assembly system - Mailah, Musa (Faculty of Mechanical Engineering, 1999)
The paper describes the design and development of a dedicatd multifunction gripper for use in a robotic assembly system. It is based on the current automated assembly system operating in an actual manufacturing environment involving the assembly of parts to be incorporated in automated teller machines (ATM). The gripper that is fixed to the wrist of the robot arm is used to handle a set of ferrous shafts and rubber rolls to be assembled via suitable assembly mechanisms. A comprehensive description of the gripper design process is given from the conceptual stage to the realization of the prototype including testing and evaluation.